2016
DOI: 10.14309/crj.2016.46
|View full text |Cite
|
Sign up to set email alerts
|

Primary Small Cell Carcinoma of the Pancreas Presenting With Likely Paraneoplastic Features

Abstract: Primary small cell carcinoma of the pancreas (SCCP) is a rare malignancy, and has been associated with paraneoplastic features in only 2 reported cases. We report a rare and fatal case of SCCP with likely paraneoplastic features in a previously well 67-year-old woman presenting with abdominal pain. She was found to have abnormal biochemical markers (hyperkalaemia and hyponatraemia) with a normal abdominal CT. Emergency laparotomy identified a mass at the head of the pancreas and liver metastases, she died soon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 7 publications
1
4
0
1
Order By: Relevance
“…Two cases have described associated paraneoplastic syndromes similar to those well recognized in small cell lung cancer [1]. Our patient passed away before further workup, but her unusual symptoms further emphasize the often atypical presentations of this malignancy.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…Two cases have described associated paraneoplastic syndromes similar to those well recognized in small cell lung cancer [1]. Our patient passed away before further workup, but her unusual symptoms further emphasize the often atypical presentations of this malignancy.…”
Section: Discussionsupporting
confidence: 56%
“…The majority of patients present with nausea, vomiting, abdominal discomfort, weight loss, and jaundice though there have been a few cases with unusual presentations such as hyperkalemia [1] and hypercalcemia [2].…”
Section: Discussionmentioning
confidence: 99%
“…34 Some rare cases of ectopic antidiuretic hormone production were described in patients with pancreatic adenocarcinoma. [35][36][37] We observed hyponatraemia in 14% of patients with early stages of pancreatic adenocarcinoma. Hyponatraemia has been identified as a negative prognostic and predictive factor in…”
Section: Discussionmentioning
confidence: 99%
“…Fewer than 50 cases have been reported in the literature; hence, there is limited knowledge about its natural history, treatment options, and outcomes. Clinically, they appear to behave in ways that resemble histologically similar SCLC including their tendency to be widely metastatic at the time of diagnosis with poor prognosis [ 1 , 2 ], better initial response to chemotherapy [ 3 ], and their association with paraneoplastic syndrome [ 4 , 5 , 6 ]. Two reviews of previously reported cases suggest average age at diagnosis in the sixth decade of life, widely varying survival, and male preponderance of cases with most tumors originating in the head of the pancreas [ 1 , 2 ].…”
Section: Discussionmentioning
confidence: 99%